2012
DOI: 10.1126/science.1224026
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial Disease and Impaired IFN-γ Immunity in Humans with Inherited ISG15 Deficiency

Abstract: ISG15 is an interferon (IFN)-α/β-inducible, ubiquitin-like intracellular protein. Its conjugation to various proteins (ISGylation) contributes to antiviral immunity in mice. We describe human patients with inherited ISG15 deficiency and mycobacterial, but not viral diseases. The lack of intracellular ISG15 production and protein ISGylation was not associated with cellular susceptibility to any viruses tested, consistent with the lack of viral diseases in these patients. By contrast, the lack of mycobacterium-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
496
5
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 486 publications
(525 citation statements)
references
References 29 publications
17
496
5
7
Order By: Relevance
“…In 1996, we jointly reported the first genetic etiology of MSMD: autosomal recessive complete IFN-γ receptor 1 (IFN-γR1) deficiency (17,18). Over the next 20 y, we and others pursued this forward genetic approach and discovered a group of 17 inborn errors of IFN-γ immunity involving nine genes (19)(20)(21)(22)(23). Some MSMD-causing genes control the production of IFN-γ; others govern its action.…”
Section: Inborn Errors Of Ifn-γ Immunitymentioning
confidence: 99%
“…In 1996, we jointly reported the first genetic etiology of MSMD: autosomal recessive complete IFN-γ receptor 1 (IFN-γR1) deficiency (17,18). Over the next 20 y, we and others pursued this forward genetic approach and discovered a group of 17 inborn errors of IFN-γ immunity involving nine genes (19)(20)(21)(22)(23). Some MSMD-causing genes control the production of IFN-γ; others govern its action.…”
Section: Inborn Errors Of Ifn-γ Immunitymentioning
confidence: 99%
“…Most recently, Bogunovic and colleagues published one critical paper in Science, providing new evidence to confirm that ISG15 acts as an extracellular cytokine and promotes IFN-γ production. More importantly, this paper shows an essential role of ISG15-regulated IFN-γ immunity against mycobacterial disease in human [9].…”
mentioning
confidence: 99%
“…As has been shown in ISG15 -/-and Ube1L -/-mice, Bogunovic et al found that cells from MSMD patients lack ISG15 expression after IFNα/β stimulation, but other ISGs are induced normally, confirming that ISG15 is not essential to elicit an IFN response [2]. Furthermore, patient cell lines are not more susceptible to infection by viruses such as herpes simplex virus, Sindbis virus and vesicular stomatitis virus.…”
Section: Christian Pohl and Ivan Dikicmentioning
confidence: 85%
“…Considering the limited number of viral infections common to both mice and man, it has been difficult to extrapolate what the in vivo functions of ISGylation might be in humans. The Bogunovic et al [2] study is a clear step forward in our understanding of ISG15 function in infection biology. By analysing patients with the rare paediatric syndrome, Mendelian susceptibility to mycobacterial disease (MSMD), they identified mutations in ISG15 that lead to its loss of expression and suggest that these mutations cause the disease.…”
Section: Hot Off the Pressmentioning
confidence: 99%
See 1 more Smart Citation